Optimization for Kinematics Accuracy Reliability of Beating-up Mechanism of High-speed Rapier Loom (Journal of Fiber Bioengineering and Informatics, 2015)
The problems of reliability, stability and kinematics accuracy of domestic high-speed rapier loom are\rurgent to be solved. For the limitations of used methods of solving kinematics accuracy reliability, the\rmathematical solution model and index of kinematics accuracy reliability of beating-up mechanism were\restablished based on the geometrical principle of reliability index. The particle swarm optimization\rwas improved. Then using improved particle swarm optimization, the kinematics accuracy reliability\rof beating-up mechanism of high-speed rapier loom was optimized. The computational precision and\reffectiveness of solving are both improved. Thus a new valid method is provided for the solution of\rkinematics accuracy reliability of beating-up mechanism of high-speed rapier loom.